Malignant schwannoma of the soft palate: A case report - Rego, João (2011)
Schwannomas are benign nerve-sheath tumors arising from Schwann cells of sheaths of peripheral nerves.They may take origin from many different nerve types and may be found intra-, extra-, or transcranially. A rare site for schwannoma is oral cavity.The prognosis of schwannoma is favorable and conservative surgical removal is the treatment of choice.Malignant transformation of benign schwannomas is rare and despite postoperative radiation therapy and chemotherapy, malignant schwannomas are usually resistant to both.We report a case of a malignant schwannoma of the palate in a 43 year old man with a 1 year history of disphagia and disphonia. He was submitted to surgical removal and postoperative radiation therapy. After 1 year there are no signs of recurrence. The significance of this case lies in the unusual diagnosis of malignant schwannoma in a solitary and encapsulated aparently benign mass.